EXPLORING THE ROLE OF MENTAL HEALTH: THE RELATIONSHIP BETWEEN DESPOTIC LEADERSHIP, EMPLOYEE WELL-BEING, AND JOB SATISFACTION - Ramadhani, Hanif Fariz; Daud, Ilzar; Marumpe, Dody Pratama; Hasanudin, Hasanudin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to investigate the role of mental health as a mediator in the relationship between despotic leadership and employee well-being on job satisfaction. Specifically, it examines how despotic leadership and employee well-being affect the mental health and job satisfaction of officers in the Civil Service Police Unit (Satpol PP) Office of West Kalimantan Province. The study uses a quantitative approach with a sample of 207 officers who have worked for three years or more. The data was processed and analyze using AMOS 26 and structural equation model (SEM). The results of this study found that despotic leadership and employee well-being have a significant influence on job satisfaction. Additionally, this research successfully tested the role of mental health as a mediator in the relationship between despotic leadership, employee well-being, and job satisfaction, with the findings showing that mental health has a positive and significant impact. The study will contribute to the existing literature by providing a nuanced understanding of the interplay between despotic leadership, employee well-being, and mental health on job satisfaction. The research findings can have significant implications for organizational practices and policies aimed at improving employee job satisfaction and overall well-being.